Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.vas.2018.11.004
|View full text |Cite|
|
Sign up to set email alerts
|

First isolation of a methicillin-resistant Staphylococcus aureus from bovine mastitis in Argentina

Abstract: This research communication describes the first isolation of a methicillin-resistant Staphylococcus aureus (MRSA) from cow's mastitic milk in Argentina. Bovine mastitis causes important economic losses in the dairy industry and the most commonly isolated bacteria from bovine mastitis are staphylococci . The mec A gene present in MRSA bacteria confers resistance to almost all β -lactam antibiotics, the most frequent drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Staphylococci were found the most common pathogens isolated from milk samples taken from cows with clinical and subclinical mastitis across several countries. Staphylococcus aureus is the main pathogen of this genus, being responsible for up to 40% of all mastitis cases in some geographic regions (11). A thorough under-standing on antibiotic resistance mechanisms is paramount to developing new strategies for preventing the emergence of resistance (12).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococci were found the most common pathogens isolated from milk samples taken from cows with clinical and subclinical mastitis across several countries. Staphylococcus aureus is the main pathogen of this genus, being responsible for up to 40% of all mastitis cases in some geographic regions (11). A thorough under-standing on antibiotic resistance mechanisms is paramount to developing new strategies for preventing the emergence of resistance (12).…”
Section: Introductionmentioning
confidence: 99%
“…Sizes of squares indicate the weight of each study based on sample size. The diamond indicates the estimated pooled effect size; CI = confidence interval Overall (I^2 = 97•48%, p = 0•00) Buyukcangaz et al, 2013 Zayda et al, 2020 Kwon et al, 2005 Zaatout et al, 2020 Awad et al, 2017 Guimarães et al, 2017 Elhaig and Selim, 2015 El-Ashker et al, 2015 Akkou et al, 2018 Algammal et al, 2020 Tavakol et al, 2012 Oreiby et al, 2019 Chandrasekaran et al, 2014 Rossi et al, 2019 Pu et al, 2014 Yang et al, 2020 Dan et al, 2019 Sayed, 2016 Klibi et al, 2018 Study Havaei et al, 2015 Enany et al, 2013 Elkenany, 2018 Nazir et al, 2017 Hamid et al, 2017 Girmay et al, 2020 Kutar et al, 2015 Jamali et al, 2014 Wang et al, 2018 Yi et al, 2018 Pehlivanoglu and Yardımcı, 2012 El-Ashker et al, 2020 Zhang et al, 2016Gindonis et al, 2013Käppeli et al, 2019Schabauer et al, 2018Benhamed and Kihal, 2013Mistry et al, 2016Abed et al, 2018Zuniga et al, 2020Shah et al, 2019Khan et al, 2020 Haveri et al, 2008Song et al, 2016Silva et al, 2014Heidari et al, 2011Ismail, 2017 Shrivastava et al, 2016Ganai et al, 2016Srednik et al, 2018Hanon, 2016Mahanti et al, 2020Kaszanyitzky et al, 2007Abd El-Tawab et al, 2016Suleiman et al, 2012Asfour, 2011 Abd Al-Azeem et al, 2013Sheela et al, 2016Hoque et al, 2018Srednik et al, 2019Kumar et al, 2011Kumar et al, 2010 Schmidt et al, 2015Moon et al, 2007Kumari et al, 2020Patel et al, 2017Salam, 2015Li et al, 2015…”
mentioning
confidence: 99%
“…Kumar et al, 2010Schabauer et al, 2018Heidari et al, 2011Hamid et al, 2017 Subtotal (I^2 = 95•03%, p = 0•00)Gindonis et al, 2013Kumar et al, 2011 Algammal et al, 2020Kaszanyitzky et al, 2007Elhaig and Selim, 2015Hoque et al, 2018Käppeli et al, 2019Salam, 2015Zaatout et al, 2020Enany et al, 2013Suleiman et al, 2012Dan et al, 2019El-Ashker et al, 2020Yang et al, 2020 Haveri et al, 2008Havaei et al, 2015Mahanti et al, 2020Sheela et al, 2016Sayed, 2016Zayda et al, 2020Khan et al, 2020Oreiby et al, 2019Srednik et al, 2019Srednik et al, 2018Rossi et al, 2019Patel et al, 2017Awad et al, 2017Buyukcangaz et al, 2013Moon et al, 2007 Schmidt et al, 2015Chandrasekaran et al, 2014Mistry et al, 2016 Subtotal (I^2 = 97•73%, p = 0•00) Ismail, 2017Asfour, 2011Wang et al, 2018Yi et al, 2018Li et al, 2015Song et al, 2016Tavakol et al, 2012Klibi et al, 2018-2015 Pehlivanoglu and Yardımcı, 20122005-2011…”
mentioning
confidence: 99%
“…All S. aureus isolates detected in this study were susceptible to erythromycin and clindamycin, and showed lower resistance to penicillin resistance than in previous years (23.1%) [ 34 ]. We reported the first MRSA from milk samples in Argentina [ 35 ], which would indicate a change or evolution in antimicrobial resistance. The emergence of MR is due to the acquisition and insertion of the SCC mec into the chromosome.…”
Section: Discussionmentioning
confidence: 99%